PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PERKEBUNAN KABUPATEN MUSI BANYUASIN - Ellisyah Mindari (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2021)
This study aims to analyze the effect of motivation (x1) and work discipline (x2) on work productivity (y) of employees, either together or partially. The research method uses survey research methods (quantitative). According to the level of explanation, formulation of the problem is associative with the form of a causal relationship. The data were tested for validity, reliability, multiple regression analysis, determinant coefficients, Ftestand ttest. The multiple regression equation is Y = 20,956 + 0,334x1 + 0,133x2. Value of the determinant coefficient is 0,307, which means that y is explained by x1 and x2 of 30.7%, while 69.3% is explained by other factors. The results of the ftest show that Fcount 17,539 > Ftable 3,112 which means that there is an effect of x1 and x2 together on y and a significant value of 0,000 <α(0,05) which indicates that there is a significant effect. The motivation variable has a tcount value of 5,407 > ttable 1,991 which means that there is a partial effect of x1 on y and the value of Sig t is 0,000 <α(0,05) meaning that there is a significant effect. Meanwhile, tcount value of the work discipline variable is 1,488 < ttable 1,991 which can be interpreted that there is no partial effect of x2 on y and the value of Sig t is 0,141 >α(0,05) which means that x2 has no significant effect. Keywords: Work Discipline, Work Productivity, Motivation.